Burst mode optical receiver for ethernet passive optical network - Duan, Lian (2009)
The explosive growth of the internet demand high-speed data transmission due to the multimedia and telecommunication. To break the existing speed bottleneck with the traditional broadband solutions such as Digital Subscriber Line (DSL) and Community Antenna Television (CATV), Fiber-To-The-Home (FTTH) using optical fiber has been developed as a feasible solution for the Local Area Network (LAN). A popular implementation of the FTTH is the Ethernet Passive Optical Network (EPON) system. Two versions of the circuit are designed to operate with 2.5 Gbps data for the burst mode optical receiver inside the Optical Line Terminal (OLT) in the EPON system. The second version of the circuit is an improved version of the first with an added automatic gain control block to increase the dynamic range. The key idea in the two designs is to generate an internal reset signal based on the magnitude of the input signal in a feedforward configuration.